C12 A new setup of the discrimination test as part of an assessment battery for phenotyping minipigs transgenic for huntington's disease. (13th September 2016) - Rieke, Lorena; Schramke, Sarah; Matheis, Tamara; Schubert, Robin; Freisfeld, Frauke; Motlik, Jan; Schuldenzucker, Verena; Reilmann, Ralf
Abstract : Backround: The Libechov tgHD minipig model is currently translated to first preclinical studies in HD. We here introduce a new semi-automated setup of the discrimination test as part of an assessment battery for phenotyping minipigs. The discrimination test primarily assesses cognitive dysfunction. Objective: To improve the feasibility and sensitivity of the discrimination test in minipigs. Methods: Thirty-two minipigs – 18 wt and 14 tg (with an N-terminal fragment of the huntingtin gene coding for 548 aa with 124Q) performed a colour discrimination test using a setup previously published. Based on experiences, a new semi-automated computer controlled setup was developed, which replaces the manual assessments with three identical boxes of different colour. The new setup permits displaying visual cues such as different colours but also more complex cues such as various shapes and figures and variation of exposure times. In addition, minipig behaviour may be assessed using computerised sensors. Results: The published discrimination test showed that both the wt and tgHD minipigs are able to differentiate between the three colours. Advantages and perspectives of the novel setup are presented. Conclusion: While the implementation of the published discrimination test is feasible and well tolerated, a novel semi-automated test will expand the cognitive features that can be tested, e.g. by using other colours, different shapes or exposure times. Acknowledgement: This study was funded by the CHDI Foundation.